Darmstadt Rotor No. 2, III: Experimental Analysis of an Aft-Swept Axial Transonic Compressor Stage - Stephan Kablitz; Jörg Bergner; Dietmar K. Hennecke; Manfred Beversdorff; Richard Schodl (International Journal of Rotating Machinery)
At Darmstadt University of Technology (Darmstadt, Germany), the Department of Gas Turbines and Flight Propulsion operates a single-stage transonic compressor test stand. Its main purpose is to provide a database for the validation of computational fluid dynamics codes. In addition, it serves as a testbed for new materials and also for the development of new measurement techniques. After setting up the test rig with a baseline rotor (Rotor No. 1), a titanium bladed disk with conventional radially stacked blade sections, a new rotor (Rotor No. 2) was designed, with the addition of considerable amounts of aft sweep and backward lean. The new rotor's flow field and mechanical properties were investigated by using various measurement techniques, including a laser-2-focus setup.